Experimental Study Of An Inlet Guide Vane Design (IGVD) For Emulsified Biofuel Application In Diesel Engine - Adnan, Nahwan Hussaini (Universiti Sains Malaysia, 2017)
The diesel engine is one of the need in many industries including automotive, marine and others. In this project, the main focus was to design and produce the guide vanes to improve the performance of diesel engines. The scope of this study was to investigate the effect of different number of vanes and angle of guide vanes towards performance of L70AE Yanmar diesel engine. In this study, nine samples of guide vanes have been designed and produced. The different angles of the guide vanes that have been produced were 20˚, 25˚, 30˚, 35˚ and 40˚, while different number of guide vanes also designed and produced were 3, 4, 5 and 6 vanes. Alternative fuels also has been widely used in various industries for various purposes because fossil fuel resources are dwindling. Thus, fuels such as bio-oil emulsion, has been used to replace diesel fuel. In this study, emulsified biofuel was produced by using palm oil that has been mixed with water. The mixture was blended using an ultrasonic homogenizer. Emulsion between oil and water able to produce the phenomenon of micro explosions. The different percentage of water in oil solution would give a different effect. Thus the properties each percentage of 1-5% water content samples were studied, including the size of microstructure, density and calorific value. Emulsified biofuel with 5% of water content has a size about 4μm, (in the range to produce the phenomenon of micro explosions). The sample of design guide vanes were tested to obtain the mass flow rate of fuel, engine torque, brake power, brake specific fuel consumption, brake thermal efficiency and brake mean effective pressure by using emulsified biofuel with 5% water content. The best diesel engine performance was observed at the optimum conditions of 3 number of vane and 40 degree angle of vane using the emulsified biofuel at 5% water composition. Approximately torque produced is about 14Nm, brake power is 5kW, brake specific fuel consumption is 0.4kg / kwh, brake thermal efficiency is 24% and brake mean effective pressure is 280kPa.